Commentary on Morreim's " So You Think You Know Who's the 'Legally Authorized Representative': Clinical Research Hits a Snag". - Serpico, Kimberley (Journal of Law, Medicine & Ethics)
In response to the article So You Think You Know Who's the "Legally Authorized Representative": Clinical Research Hits a Snag, this invited commentary draws attention to the practical realities that are overlooked in the paper's examination of enrolling research participants without decisional capacity to provide their own consent. In such scenarios, the participant's Legally Authorized Representative (LAR) is co-enrolled to consent on the participant's behalf. Implementation of a research-based LAR is a two-part process that involves identifying the LAR according to legal hierarchy and performing a capacity assessment to determine whether the prospective participant requires an LAR. The paper makes several comparisons between standard care and research approaches to these decisions, most of which the author deems inadequate for clinical research contexts, and suggests that navigating this process may pose "unexpected legal and ethical hazards" for researchers. By offering a practitioner's perspective in this commentary, I hope to bring clarity to this argument by explaining from direct experience how LAR implementation includes much greater collaboration and thought partnership between researchers and IRBs than the author gives credit for.